1987
DOI: 10.1136/jcp.40.11.1287
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of type III intestinal metaplasia in predicting risk of gastric carcinoma.

Abstract: Although the association between intestinal metaplasia and gastric carcinoma has long been recognised,' the prevalence of intestinal metaplasia in benign gastric conditions has precluded its use as an aid to the diagnosis of gastric carcinoma. Recent work has focused on the subtyping of intestinal metaplasia using mucin histochemistry. One

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 14 publications
(1 reference statement)
4
37
1
Order By: Relevance
“…In these patients, we therefore suggest a thorough endoscopic follow-up or, preferably, treatment of the promotor of regeneration, the HP gastritis. This holds true especially when IM of the enterocolic type (type III), which is said to show a greater risk for the development of gastric carcinoma, is detected [19,20,23,[51][52][53][54], The results reported by other groups, however, have failed to support this hypothesis [55][56][57][58][59], In conclusion, we might state that, although the causative role of HP in the development of IM cannot be proven, and other factors like NSAID and duodenogastral bile reflux surely have to be taken into account, our data do support the hypothesis that HP plays an important part in the development of antral IM. Another important ques tion urgently awaiting an answer is whether by eradicating HP the development of IM might be reduced.…”
Section: Discussioncontrasting
confidence: 42%
“…In these patients, we therefore suggest a thorough endoscopic follow-up or, preferably, treatment of the promotor of regeneration, the HP gastritis. This holds true especially when IM of the enterocolic type (type III), which is said to show a greater risk for the development of gastric carcinoma, is detected [19,20,23,[51][52][53][54], The results reported by other groups, however, have failed to support this hypothesis [55][56][57][58][59], In conclusion, we might state that, although the causative role of HP in the development of IM cannot be proven, and other factors like NSAID and duodenogastral bile reflux surely have to be taken into account, our data do support the hypothesis that HP plays an important part in the development of antral IM. Another important ques tion urgently awaiting an answer is whether by eradicating HP the development of IM might be reduced.…”
Section: Discussioncontrasting
confidence: 42%
“…IM type I in these studies has been found to be more frequently associated with benign gastric conditions, while type 111 was more often associated with stomach cancer (Sipponen et al, 1980;Silva and Filipe, 1986;Rokkas et al, 1991;Filipe et al, 1985;Turani et al, 1986;Kini et al, 1990). Although 2 earlier cohort studies concluded that subtyping of IM in endoscopic biopsies was of only limited value in identifying patients who required longterm follow-up, this was based on a case or two without statistical evaluation (Ectors and Dixon, 1986;Ramesar et al, 1987) and therefore is not convincing evidence.…”
Section: Discussionmentioning
confidence: 94%
“…The risk of gastric cancer is proportional to the extent of metaplasia [49]. However, follow-up studies of type III metaplasia did not show an increased risk of gastric carcinoma [51]. Examination of microcarcinomas less than 5 mm in diameter revealed that prominent metaplasia accompa- nied tubular carcinoma but not mucocellular (signet-ring cell) carcinoma [52].…”
Section: Intestinal Metaplasia (Im)mentioning
confidence: 99%